Identity-supportive nursing of patients with dementia in nursing homes - Drageset, Ingrid Marie Saga; Normann, Hans Ketil; Elstad, Ingunn (Universitetsforlaget, 2015)
This is the accepted manuscript version. Published version available at http://www.idunn.no/nsf This article aims to explore how nursing can support a sense of continuity and identity in patients with advanced dementia disease, living in nursing homes. Fourteen carers and managers in two nursing homes in northern Norway were interviewed. The analysis and discussion are based on the theoretical concepts of identity, continuity and person-centred nursing. This study concludes that an awareness of an individual's earlier life may be practically expressed in person-centred nursing, and may support continuity in the patient´s life even after moving into the nursing home. Documentation, professional development, and the organisation of the nursing home are important elements to ensure this awareness. Whilst on-going competence building in the nursing home is necessary, the value of local knowledge among the staff is also emphasized. Before a person moves to a nursing home it would be useful for staff to visit the person's home, gather information from the person and their family, and establish a relationship that can give a sense of security. In the nursing home, a feeling of belonging and identity can be enhanced through daily activities, personal care and mealtimes. The importance of reinforcing a sense of belonging in patients with dementia disease is highlighted